84. Functional evaluation of central cholinergic circuits in patients with Parkinson's disease and freezing of gait. Issue 1 (January 2015) - Dubbioso, R.; Picillo, M.; Amboni, M.; Iodice, R.; Barone, P.; Santoro, L.; Manganelli, F.
<x xml:space="preserve">Abstract</x> Abnormalities of cholinergic circuitries may be at the basis of cognitive dysfunction, gait disorders, and falls and they may also be important for freezing of gait (FOG). Aim of this study is the evaluation of central cholinergic circuits by means of short latency afferent inhibition (SAI) technique in patients with Parkinson's disease (PD) and freezing of gait (FOG+). We applied the SAI technique in 14 FOG+ patients, in 10 patients without freezing (FOG−) and in 11 age-matched normal controls. All PD patients also underwent a comprehensive battery of neuropsychological tests. Mean SAI was not significantly different in FOG+ patients when compared with FOG− patients and controls. Neuropsychological examination showed mild cognitive impairment (MCI) in 10 out of the 14 FOG+ patients, and in 1 out of the 10 FOG−. Notably, the pattern of cognitive impairment included a variable degree of deficits in executive and visuospatial domains. Our SAI findings suggest the integrity of cholinergic circuits in PD patients with FOG. In addition, neuropsychological findings provide further evidence of executive dysfunction in the pathogenesis of FOG.